Analysis of the Mechanism of Ground Fissures in the Nairobi–Malaba Railway Rift Valley Area in Kenya - Hao, Bing; Zhou, Zhenghua; Li, Yuandong; Li, Xiaojun; Liu, Xujin; Han, Yi; Jin, Liguo (Frontiers in Earth Science, 2022)
During the rainy season from March to May 2018, four ground fissures were generated in the rift valley area along the first phase of the Nairobi–Malaba Railway in Kenya, among which the ground fissures B3 highway, DK76, and DK77 were larger in scale, which seriously endangered the safety of the railway. According to the author’s previous study, the ground fissure B3 highway belongs to a typical fault-type fissure, and the ground fissures DK76 and DK77 are qualitatively concluded to be generated under the groundwater erosion of collapsible soils. To quantitatively summarize the mechanism of ground fissures, DK76 and DK77, physical model tests on the overlying soil properties, compactness, the intersection angle between hidden cracks and the water flow direction, the height of confined water level, and the groundwater flow rate are conducted to analyze the effect of these factors on the formation and expansion of ground fissures. The test results show that the soil with strong collapsibility under the action of underground erosion produces fissures, collapses, and holes similar to those in the rift valley area along the first phase of the Nairobi–Malaba Railway in Kenya; the loose overburden is conducive to the occurrence of surface collapse; the collapse of the soil surface is the most severe when the underlaid cracks are parallel to the water flow direction; the higher confined water level and faster inflow rate will aggravate the collapse of the overlying soil layer.